A SYSTEMIC REVIEW ON USE OF HERBAL MEDICINES IN THE PREVENTION AND TREATMENT OF ALZHEIMER’S DISEASE (International Journal of Food and Nutritional Sciences, 2022)
Alzheimer's disease, also known as dementia (AD) is a multifaceted, progressive neurodegenerative illness marked by diminished memory, personality changes, and cognitive impairment. While the specific etiology of Alzheimer's disease is unknown, new research suggests that lifestyle, food, environmental, and hereditary variables all have a role in disease progression. To present, pharmaceutical therapies have had no effect on disease progression. Over the last decade, more than 200 potential drugs have failed clinical trials, indicating that the illness and its causes are likely to be complicated. Medicinal plants and herbal therapies are gaining popularity as complementary and alternative interventions, and they can be used to produce medication candidates for Alzheimer's disease.